Reconstructing the Concept of Marriage: Preventing the Spread of Unregistered Marriages through Legal Literacy and Sharia Ethics - Suwarno; Hudallah Hudallah (Penerbit Hellow Pustaka, 2025)
Although a marriage may be deemed valid under Islamic Sharia provided it fulfills the essential pillars (arkan) and conditions (shurut) (such as the presence of a guardian (wali) and witnesses) the practice of unregistered marriage (nikah siri) remains a profound socio-legal concern. This paper argues that while religiously legitimate, unregistered marriages often fail to serve as a sustainable solution for marital relationships. No religious framework inherently recommends bypassing legal registration. The absence of official documentation creates a significant legal vacuum, leading to detrimental consequences primarily for women and children regarding their civil rights and inheritance. This study emphasizes the urgency of preventing the normalization of unregistered marriages. It advocates for a deeper understanding of the